Galectin-3, Possible Role in Pathogenesis of Periodontal Diseases and Potential Therapeutic Target - Velickovic, Milica; Arsenijevic, Aleksandar; Acovic, Aleksandar; Arsenijevic, Dragana; Milovanovic, Jelena; Dimitrijevic, Jelena; Todorovic, Zeljko; Milovanovic, Marija; Kanjevac, Tatjana; Arsenijevic, Nebojsa (Frontiers in Pharmacology, 2021)
Periodontal diseases are chronic inflammatory diseases that occur due to the imbalance between microbial communities in the oral cavity and the immune response of the host that lead to destruction of tooth supporting structures and finally to alveolar bone loss. Galectin-3 is a β-galactoside-binding lectin with important roles in numerous biological processes. By direct binding to microbes and modulation of their clearence, Galectin-3 can affect the composition of microbial community in the oral cavity. Galectin-3 also modulates the function of many immune cells in the gingiva and gingival sulcus and thus can affect immune homeostasis. Few clinical studies demonstrated increased expression of Galectin-3 in different forms of periodontal diseases. Therefore, the objective of this mini review is to discuss the possible effects of Galectin-3 on the process of immune homeostasis and the balance between oral microbial community and host response and to provide insights into the potential therapeutic targeting of Gal-3 in periodontal disease.